2016
DOI: 10.3399/bjgp16x683449
|View full text |Cite
|
Sign up to set email alerts
|

International variation in adherence to referral guidelines for suspected cancer: a secondary analysis of survey data

Abstract: BackgroundVariation in cancer survival persists between comparable nations and appears to be due, in part, to primary care practitioners (PCPs) having different thresholds for acting definitively in response to cancer-related symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 20 publications
0
39
0
2
Order By: Relevance
“…Guidelines may lack efficacy if adherence is low. In their survey of 2795 GPs, NICHOLSON et al [59] reported wide international variation (24-82%) in adherence to lung cancer guidelines, with UK GP adherence significantly lower than that of other geographical regions. Authors acknowledge that lack of available guidelines may have contributed to very low rates of proposed definitive action.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines may lack efficacy if adherence is low. In their survey of 2795 GPs, NICHOLSON et al [59] reported wide international variation (24-82%) in adherence to lung cancer guidelines, with UK GP adherence significantly lower than that of other geographical regions. Authors acknowledge that lack of available guidelines may have contributed to very low rates of proposed definitive action.…”
Section: Discussionmentioning
confidence: 99%
“…Second, data prospectively documenting the degree of implementation could for each revision be extracted from the clinical DBCG database. In contrast, implementation of guidelines is frequently evaluated retrospectively using questionnaires [35]. Some limitations should be considered when interpreting our study.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 68 (27) 49 (25) 42 (21) 74 (26) 83 (41) 133 (46) 59 283 3124 60661 (31) <0.001 § † II 27 (13) 36 (14) 32 (16) 33 (17) 26 (9) 19 938 1311 55 647 (23) 274 (13) <0.001 ¶ ‡ III 64 (30) 57 (23) 56 (28) 59 (30) 84 (29) 48 (24) 54 (19) 40 (19) 5 619 (9) 486 (23) IV 62 (29) 80 (32) 50 (25) 62 (31) 94 (33) 48 (24) 54 (19) 94 453 313 (6) 560 ( (39) 68 (27) 76 (38) 72 (36) 114 (40) 81 (40) 98 (34) 70 3341 4729…”
Section: Open Accessunclassified
“…Categorising presenting symptoms into indicative or not was done pragmatically as existing guidelines for lung cancer investigation vary across ICBP jurisdictions. 36 In Norway and Victoria, a small sample size and restriction of eligibility to only surgical patients, respectively, made comparison difficult. Nonetheless, significant differences in these two jurisdictions compared with Wales were largely limited to the treatment interval alone.…”
Section: Open Accessmentioning
confidence: 99%